Hemin Covalently Functionalized Carbon Nanobranch with Enzyme‐Like and Photocatalytic Activities for Synergistic Dye Degradation and Antibacterial Therapy. (10th June 2021) - Xu, Chengjie; Zhou, Li; Zheng, Sidi; Yu, Deshuai; Tang, Yonghua; Fan, Chaoyu; Lin, Changxu; Zhou, Dongfang; Lin, Youhui
Abstract: The development of artificial enzymes with excellent enzyme‐like activities and unique features is highly desirable for their practical applications. Herein, a one‐pot facile method to synthesize hemin covalently functionalized carbon nanobranch (CN‐hemin) via direct pyrolysis of citric acid and covalent coupling of hemin to the formed carbon skeleton, is reported. This strategy is reasonably straightforward, cheap, and environmentally friendly, without any extraneous oxidant, reductant, and harmful additives during the preparation process. Furthermore, the obtained dendritic hybrids possess good water‐solubility, intrinsic peroxidase‐like activity, and satisfactory photocatalytic performance in visible light. These extraordinary properties are mainly due to the structure of CN‐hemin which contains iron porphyrin, aromatic carbon, and citric acid residues. Most importantly, under visible light irradiation, the as‐prepared hemin‐incorporated nanohybrid can act as robust agents for synergistic dye degradation and antibacterial therapy toward Staphylococcus aureus and methicillin‐resistant S. aureus . It is expected that this study can shed valuable light on developing advanced multifunctional nanozymes with combined favorable properties for highly efficient elimination of environmental pollutants and antibacterial treatment. Abstract : The design of artificial enzymes with unique features is highly desirable. In this work, a facile and efficient pathway is developed to synthesize hemin covalently functionalized carbon nanobranch by one‐pot pyrolysis of citric acid and hemin. The prepared CN‐hemin shows good water‐solubility, and excellent photocatalytic and peroxidase‐like properties, which can be used for synergistic dye degradation and antibacterial applications.